2019
DOI: 10.1155/2019/8759231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vascular Endothelial Growth Factor A and Selected Parameters of Coagulation and Fibrinolysis in a Group of Patients with Subarachnoid Haemorrhage

Abstract: Introduction. Subarachnoid hemorrhage (SAH) is currently one of the most serious diseases of the central nervous system. To reduce the negative consequences of SAH and help clinicians to assess the patient’s condition, there are attempts to search for new diagnostic markers, which quickly and accurately allow for the proper diagnosis. The aim of this research was the concentration and activity of Vascular Endothelial Growth Factor A (VEGF-A) and selected parameters of coagulation and fibrinolysis in the blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Prothrombin time (PT), international normalized ratio (INR), and activated partial thromboplastin time (aPTT) were all consequently within reference ranges. 35 37 42 49 50 51 53 65 66 When comparing with healthy control groups, a few studies found that aPTT tended to be shortened 37 39 and INR slightly prolonged, 37 but still within reference ranges.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prothrombin time (PT), international normalized ratio (INR), and activated partial thromboplastin time (aPTT) were all consequently within reference ranges. 35 37 42 49 50 51 53 65 66 When comparing with healthy control groups, a few studies found that aPTT tended to be shortened 37 39 and INR slightly prolonged, 37 but still within reference ranges.…”
Section: Resultsmentioning
confidence: 99%
“…32 36 39 40 41 42 43 44 In accordance with this, fibrin degradation products (FDPs) were also increased in the studies by Ebihara et al, Sasaki et al, and Tsementzis et al 40 43 62 Only two studies found a mean D-dimer within reference range. 35 57…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations